2023
DOI: 10.1002/cphc.202300545
|View full text |Cite
|
Sign up to set email alerts
|

Direct Experimental Observations of Ion Distributions during Overcharging at the Muscovite‐Water Interface by Adsorption of Rb+ and Halides (Cl, Br, I) at High Salinity

Julia Neumann,
Sang Soo Lee,
Eric J. Zhao
et al.

Abstract: Classical electric double layer (EDL) models have been widely used to describe ion distributions at charged solid‐water interfaces in dilute electrolytes. However, the chemistry of EDLs remains poorly constrained at high ionic strength where ion–ion correlations control non‐classical behavior such as overcharging, i.e., the accumulation of counter‐ions in amounts exceeding the substrate’s surface charge. Here, we provide direct experimental observations of correlated cation and anion distributions adsorbed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…20,45,67−69 At very high electrolyte concentrations (3−5 M) on mica AFM has revealed a co-ion layer, 25 and resonant anomalous X-ray reflectivity of the interface of mica with rubidium halide (RbCl) solutions revealed co-ion rich second layers. 70 The authors of the latter paper concluded that anion adsorption stabilizes the correlated cation arrangements in the Stern layer, although for a crystalline mica surface, these results are consistent with the Wigner crystal-like structures proposed in this paper for disordered substrates. As positive potential is increased, Cl − remains concentrated just above the water layer on the gold surface, followed by a Mg 2+ layer, and Mg 2+ −Cl − ion clusters also form in this this region (Figure S18a).…”
Section: Acssupporting
confidence: 79%
See 1 more Smart Citation
“…20,45,67−69 At very high electrolyte concentrations (3−5 M) on mica AFM has revealed a co-ion layer, 25 and resonant anomalous X-ray reflectivity of the interface of mica with rubidium halide (RbCl) solutions revealed co-ion rich second layers. 70 The authors of the latter paper concluded that anion adsorption stabilizes the correlated cation arrangements in the Stern layer, although for a crystalline mica surface, these results are consistent with the Wigner crystal-like structures proposed in this paper for disordered substrates. As positive potential is increased, Cl − remains concentrated just above the water layer on the gold surface, followed by a Mg 2+ layer, and Mg 2+ −Cl − ion clusters also form in this this region (Figure S18a).…”
Section: Acssupporting
confidence: 79%
“…This suggests that Cl – is weakly associated with the Mg 2+ and displaced by the AFM tip during imaging and rapidly returns to the crystal surface as the tip passes. This is not unexpected, as co-ion adsorption cannot be detected with AFM even on strongly templating crystalline surfaces at low to moderate electrolyte concentrations. ,, At very high electrolyte concentrations (3–5 M) on mica AFM has revealed a co-ion layer, and resonant anomalous X-ray reflectivity of the interface of mica with rubidium halide (RbCl) solutions revealed co-ion rich second layers . The authors of the latter paper concluded that anion adsorption stabilizes the correlated cation arrangements in the Stern layer, although for a crystalline mica surface, these results are consistent with the Wigner crystal-like structures proposed in this paper for disordered substrates.…”
Section: Resultsmentioning
confidence: 97%
“…[ 130 ] For example, some hydrogels composed of Fe 3+ and Al 3+ have an extremely fast self‐assembly speed (about 1 min) and good antibacterial activity against Escherichia coli and Staphylococcus aureus . [ 131 ] Therefore, based on the arrangement and combination of metal ions and drug, various metal–drug hydrogels with different applications, targets, and biological functions can be designed. This section focuses on these hybrid materials and their related applications.…”
Section: Metal–drug Coordination Hydrogelsmentioning
confidence: 99%